Strategies for remediation of very large deposits of mine waste : the Aitik mine, Northern Sweden - Lindvall, Manfred (Luleå tekniska universitet, 2005)
The Aitik mine, near Gällivare in Sweden, is the largest copper mine in Europe with an annual production exceeding 18 Mt of ore. After processing of the ore the residual waste material, so called tailings, are deposited in a tailings pond. In addition, 15 - 25 Mt of barren waste rock is mined annually in order to provide access to the ore. The waste rock is deposited in waste rock dumps located close to the mine. The production started 1968, and very large quantities of waste have been accumulated since. A comprehensive set of strategies for management and decommissioning of the waste deposits have been developed, based on studies, investigations and tests carried out by Boliden, as well as independent consultants and universities, since the first permit regulating reclamation issues came into force 1989. During operation of the mine, the emissions to the receiving environment are limited. During a normal year, the effluent contains less than 50 kg of copper. However the internal circulation of copper is orders of magnitude larger. This fact calls for suitable decommissioning measures to prevent an increase of the emissions after closure. Moreover, by developing and implementing strict waste management routines the potential environmental impacts can be minimized and closure costs drastically reduced. As a foundation for the test work a variety of site investigations were carried out to establish the hydrogeological and geochemical conditions. Material characterization results show that some but not all waste types and categories may cause acid rock drainage (ARD). In order to reach conclusive results extensive kinetic test periods, using column and humidity cell tests, were required in combination with geochemical modelling to provide reliable results. Results of long term weathering and leaching tests on mill tailings were compared with measured weathering rates in field. The results show that weathering in field is much slower than in lab, but that there is still a potential for generation of acid leachate in ...